Sexual health counselling in patients with spinal cord injury: Health care professionals' perspectives. (4th March 2022) - Rassem, Mariam; Siddiqui, Muhammad; Wunder, Shane; Ganshorn, Keren; Kraushaar, Jacqueline
Abstract : Objectives: We aimed to explore barriers to discussing sexual health with spinal cord injured (SCI) patients as perceived by health care professionals, to determine interest and preferences regarding further education in sexual health, and to assess the perceived need for an inpatient Sexual Health Team. Design: Pre and post surveys were completed by attendees following a 1–2 hour educational session on sexual health and SCI, assessing core elements including participant characteristics, confidence levels, and perceptions towards sexual health counselling and education. Setting: Wascana Rehabilitation Centre, a facility in Regina, SK offering inpatient and outpatient rehabilitation services in Saskatchewan. Participants: Eighty-six participants with a mean age of 39 years took part in this study. Among them, nearly half were nurses. Interventions: Educational sessions on SCI patients' sexual health. Outcome Measures: Self-administered surveys. Results: Significant differences were observed between pre- and post-session participant responses regarding their confidence levels (P < 0.001). Most participants (82.1%) had never provided sexual health counselling to SCI patients. The main perceived barrier to lack of sexual health counselling was insufficient training; the preferred learning method was via in-person workshops. The majority (80%) of participants indicated a Sexual Health Team should be created and 39.4% of participants expressed interest in becoming a member of this team. Conclusion: These results support that an educational session may help improve the confidence, knowledge, and perceptions around delivery of sexual health education of SCI patients. Study results suggest a perceived need for a Sexual Health Team and interest from health care professionals to become more involved in sexual health counselling.